The Magic Realism and the Exotic ‘Other’ in Pakistani Young Adult Fictions: an Ideological Critique of The Devil’s Kiss by Sarwat Chaddha and the Firefly in the Dark by Shazaf Fatima Haider - Dr. Asma Iqbal Qazi; Ms. Munazza Mahmood (Al-Qanṭara, 2023)
Magic realism is often taken as a literary form that challenges the norms and the peculiarities of realism, often associated with postcolonial texts, it is now commonly termed postmodernist post colonialism. Despite possessing the element of heterogeneity superadded with religious, folklorist, and cultural tales, it is still taken as a postcolonial device to address the issue of hybridity, rhetoric of identity, and fusion of binaries between fact and fiction. Recently, the notion of magic realism has been redeveloped with a twist in popular fiction in general and in young adult Anglophonic fiction in particular. Instead of treating it as a separate genre, the writers have seamlessly incorporated the notion of magic realism as a stratagem to support the main idea. By applying Wendy B Faris notion of magic realism from her seminal work Ordinary Enchantments: Magical Realism and Remystification to popular fiction such as The Devil’s Kiss by Sarwat Chaddha and The Firefly in the Dark, by Shazaf Fatima Haider, the research explores primarily how the notion of magic realism has been fused with the issues of the young adults and secondly, how have these young adult fiction incorporated the cultural and religious myth in their to endorse the element of othering Key words: young adult fiction, Anglophone fictions, magic realism, othering